Nanoparticle surface stabilizing agents influence antibacterial action - Ameh, Thelma; Zarzosa, Kusy; Dickinson, Jake; Braswell, W. Evan; Sayes, Christie M. (Frontiers in Microbiology, 2023)
The antibacterial properties of nanoparticles are of particular interest because of their potential to serve as an alternative therapy to combat antimicrobial resistance. Metal nanoparticles such as silver and copper nanoparticles have been investigated for their antibacterial properties. Silver and copper nanoparticles were synthesized with the surface stabilizing agents cetyltrimethylammonium bromide (CTAB, to confer a positive surface charge) and polyvinyl pyrrolidone (PVP, to confer a neutral surface charge). Minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and viable plate count assays were used to determine effective doses of silver and copper nanoparticles treatment against Escherichia coli, Staphylococcus aureus and Sphingobacterium multivorum. Results show that CTAB stabilized silver and copper nanoparticles were more effective antibacterial agents than PVP stabilized metal nanoparticles, with MIC values in a range of 0.003 M to 0.25 M for CTAB stabilized metal nanoparticles and 0.25 M to 2 M for PVP stabilized metal nanoparticles. The recorded MIC and MBC values of the surface stabilized metal nanoparticles show that they can serve as effective antibacterial agents at low doses. There was an observed synergistic effect of the interaction of the stabilizing agent with metal composition which boosted the antibacterial efficacy of nanoparticle.